Long-term outcomes and prognostic analysis of modified open-door laminoplasty with lateral mass screw fusion in treatment of cervical spondylotic myelopathy - Su N; Fei Q; Wang B; Li D; Li J; Meng H; Yang Y; Guo A (Dove Medical Press, 2016)
Nan Su, Qi Fei, Bingqiang Wang, Dong Li, Jinjun Li, Hai Meng, Yong Yang, Ai Guo Department of Orthopedics, Beijing Friendship Hospital, Capital Medical University, Xicheng District, Beijing, People’s Republic of China Objectives: The purpose of the present study was to explore and analyze the long-term outcomes and factors that affect the prognosis of expansive open-door laminoplasty with lateral mass screw fusion in treatment of cervical spondylotic myelopathy (CSM). Methods: We retrospectively reviewed 49 patients with multilevel CSM who had undergone expansive open-door laminoplasty with lateral mass screws fixation and fusion in our hospital between February 2008 and February 2012. The average follow-up period was 4.6 years. The clinical data of patients, including age, sex, operation records, pre- and postoperation Japanese Orthopedic Association (JOA) scores, cervical spine canal stenosis, and cervical curvature, were collected. Increased signal intensity (ISI) on T2-weighted magnetic resonance imaging and ossification of the posterior longitudinal ligament were also observed. Paired t-test was used to analyze the treatment effectiveness and recovery of neuronal function. The prognostic factors were analyzed with multivariable linear regression model. Results: Forty-nine patients with CSM with a mean age of 59.44 years were enrolled in this study. The average of preoperative JOA score was 9.14±2.25, and postoperative JOA score was 15.31±1.73. There was significant difference between the pre- and postoperative JOA scores. The clinical improvement rate was 80.27%. On follow-up, five patients had complaints of neck and shoulder pain, but no evidence of C5 nerve palsy was found. Developmental cervical spine canal stenosis was present in all patients before surgery. Before surgery, ISI was observed in eight patients, while ossification of the posterior longitudinal ligament was found in 12 patients. The average of preoperative cervical curvature was 21.27°±8.37° and postoperative cervical curvature was 20.09°±1.29°, and there was no significant difference between the pre- and postoperative cervical curvatures. Multivariable linear regression analysis results showed that the postoperation JOA scores were significantly affected by age, preoperative JOA scores, and preoperative ISI. Except one case of epidural hematoma, there were no complications associated with the surgery. Conclusion: Treatment of CSM with posterior open-door laminoplasty with lateral mass screw fusion is effective with few complications. In addition, the normal cervical lordosis was well maintained. Age, preoperative JOA scores, and preoperative ISI were the independent factors that significantly affect disease prognosis and surgical outcomes. Keywords: cervical spondylotic myelopathy, laminoplasty, lateral mass screw, prognostic factors, ossification of the posterior longitudinal ligament, JOA scores